Digital-Based Integrative Learning Strategies At Madrasah Ibtidaiyah: Forming Holistic Muslim Students In The Digital Era - Ridhwan M Daud (Barkah Publishing, 2025)
: Madrasah Ibtidaiyah (MI) plays a strategic role in shaping holistic Muslim individuals from an early age through the integration of general education with Islamic values. Facing digital transformation and global challenges, MI is required to implement innovative, engaging, and contextual learning approaches. One effective strategy is the use of simple digital media such as interactive PowerPoint presentations, learning videos, educational Islamic apps, and audio materials. These media have been proven to increase learning motivation, support visual-auditory learning styles, and instill Islamic values in an engaging manner. MI also emphasizes integrated thematic learning and a play-while-learning approach that is appropriate to children's developmental stages. Teachers play a crucial role as educators, character builders, and moral role models, shaping students holistically. While challenges such as limited technological resources and a lack of teacher training remain, these can be addressed through continuous professional development and optimal utilization of available resources. With the right strategy, MI can produce a generation that is not only intellectually intelligent but also morally and spiritually strong and ready to face the challenges of the times.